Paradigma Pemahaman Mahasiswa Mengenai Pelecehan Seksual di Lingkungan Kampus - Pinkky Angela Maulydia; Zahrotun Nisa (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2023)
This paper aims to provide education and understanding of forms of sexual harassment, because it is felt that with education about sexual harassment female students know how to prevent and protect themselves in order to avoid cases of sexual harassment in the campus environment. This problem is focused on women who have always been subject to property for sexual treatment. In order to approach this problem, theoretical references from Collier 1992 were used. The data was collected through the results of a questionnaire taken from several students' answers throughout Indonesia and then analyzed quantitatively and collected direct opinions from several students using qualitative analysis. This study concludes that women have always been the object of sexual harassment, this has motivated students to raise awareness and try to prevent this from happening. Therefore prevention efforts can be prevented from the smallest thing, namely yourself.